(untitled) (Research, Society and Development, 2022)
This study aimed to describe through the literature the knowledge of the dentist in relation to Ankyloglossia and the importance of early diagnosis through the Linguinha Test in Primary Care throughout the country. A "scoping review" was carried out, with the selection of 08 articles published from 2011 to 2019. With the mapping of the results, the thematic axes were constituted: linguinha test and its relationship with professionals; ankyloglossia; oral health and maternal-infant network. The data showed that there is little knowledge on the part of professionals in relation to the tongue test and ankyloglossia and that the dentist is little inserted in the maternal and child network within the scope of Primary Care. It was concluded that there is not a correct approach regarding the integrality and insertion of the oral health team with the family health team when it comes to the maternal and child network. In addition, it was observed that the CD does not have sufficient knowledge and does not perform the Linguinha Test in the Basic Health Unit.